Anaplastic Ventricular Adenocarcinoma in a Blue and Gold Macaw (Ara ararauna) - Anjos, Bruno L.; Diefenbach , Aline; Rissi , Daniel R.; Lovato , Maristela; Flores , Tamara; Pereira , Larissa Q.; Kommers, Glaucia D. (Brazilian Journal of Veterinary Pathology, 2012)
A case of anaplastic ventricular adenocarcinoma in an adult, female captive blue and gold macaw (Ara ararauna) is reported. The bird died suddenly and was submitted to necropsy. The carcass was in poor body condition. A pale, firm neoplastic mass was observed infiltrating the wall of the proventricular-ventricular junction. Histologically, the neoplasm consisted of a poorly demarcated and highly invasive proliferation of cuboidal to columnar neoplastic epithelial cells arranged into small groups and admixed with a dense desmoplastic reaction. Numerous neoplastic cells showed a finely fibrillar, Alcian blue-positive cytoplasmic material. Neoplastic cells were strongly positive for pancytokeratin and negative for vimentin. The diagnosis of anaplastic ventricular adenocarcinoma was based on histological, histochemical, and immunohistochemical findings. These neoplasms are uncommon in psittacine birds and to the best of our knowledge have not been reported in this species.